2015
DOI: 10.1111/cea.12526
|View full text |Cite
|
Sign up to set email alerts
|

Distal airways are protected from goblet cell metaplasia by diminished expression of IL‐13 signalling components

Abstract: These data indicate that distal airways might be less sensitive to IL-13-induced GC metaplasia and mucus production through lower expression of IL-13Rα1 and attenuated activation of downstream signalling. This might represent a protective strategy to prevent mucus plugging of distal airways and thus impaired ventilation of attached alveoli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…Epithelial cells from COPD were obtained from the large bronchus, whereas samples from transplant donor controls were obtained from the trachea/main stem area. However, goblet cell density is decreased from proximal to distal airways [34, 35], and distal airways have been shown to be less prone for goblet cell metaplasia by diminished expression of IL-13 signaling components, including IL-13 receptor IL-13Rα1, SPDEF, and FOXA3 [36]. These considerations support our conclusion that patients with COPD have an increased expression of SPDEF and MUC5AC compared to controls and suggest that our results might even be an underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial cells from COPD were obtained from the large bronchus, whereas samples from transplant donor controls were obtained from the trachea/main stem area. However, goblet cell density is decreased from proximal to distal airways [34, 35], and distal airways have been shown to be less prone for goblet cell metaplasia by diminished expression of IL-13 signaling components, including IL-13 receptor IL-13Rα1, SPDEF, and FOXA3 [36]. These considerations support our conclusion that patients with COPD have an increased expression of SPDEF and MUC5AC compared to controls and suggest that our results might even be an underestimation.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that excessive production of mucins leads to stress responses in the ER, the so called unfolded protein response (UPR) [28,51], and that this is necessary to maintain proper folding of mucins and therefore the secretory capacity of goblet cells (Figure 1) [52][53][54]. Excess ER stress can further increase inflammation by activation of nuclear factor kappa B (NFκB) and CAAT-enhancer-binding protein homologous protein (CHOP) and can even induce apoptosis.…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 99%
“…Increased IRE-1β expression mediates IL-13 dependent splicing of the ER stress associated XBP-1 gene linking mucus production and ER stress. By this, IRE1β also regulates anterior gradient protein homolog 2 (Agr2), which belongs to the protein disulfide isomerase (PDI) family and resides to the ER [51,58]. PDI proteins support the transition of proteins to the ER by the rearrangement of disulfide bonds in incorrectly folded substrate proteins [59].…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 99%
“…tobacco smoke) can trigger the above-named symptoms. The presence of lym-phocytes, eosinophils, and mast cells, along with epithelial desquamation, goblet cell hyperplasia, and thickening of the submucosa have been associated with the main physiologic abnormalities of the disease, namely airway obstruction and AHR [20,77,78].…”
Section: Il-13 In Asthmamentioning
confidence: 99%
“…Therefore IL-13 was suggested as a plausible candidate player in the development of allergic airway responses due to a high degree of similarity between IL-13 and IL-4. Thereafter, it was demonstrated separately by two groups of researchers that specifi c blockade of IL-13 by administration of a soluble form of the IL-13Ra2 chain to allergen-challenged mice, in a way that only binds with IL-13 and not IL-4, reversed Airway HyperResponsiveness (AHR) and mucus production [20]. It also has been shown that acute administration of IL-13 itself was suffi cient to recapitulate many features of the allergic phenotype, such as AHR, eosinophilic infl ammation, and mucus cell hyperplasia in non-immunized mice or recombination-activating gene-defi cient mice [21,22].…”
Section: Introductionmentioning
confidence: 99%